2010
DOI: 10.1088/0004-637x/715/1/300
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Streamer Blobs Into the Heliosphere

Abstract: In this paper, we use coronal and heliospheric images from the STEREO spacecraft to track streamer blobs into the heliosphere and to observe them being swept up and compressed by the fast wind from low-latitude coronal holes. From an analysis of their elongation/time tracks, we discover a 'locus of enhanced visibility' where neighboring blobs pass each other along the line of sight and their corotating spiral is seen edge on. The detailed shape of this locus accounts for a variety of east-west asymmetries and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 23 publications
1
51
0
Order By: Relevance
“…Similarly, small events are also detected with heliospheric imagers Sheeley and Rouillard, 2010) as well as in the corona, including eruptions from ephemeral regions and narrow CMEs Robbrecht, Berghmans, and Van der Linden, 2009;Schrijver, 2010), blowout Xray jets (Moore et al, 2010(Moore et al, , 2013, and streamer blobs (Wang, Zhang, and Shen, 2009;Sheeley et al, 2009). In parallel, much smaller FRs than typical MCs have been detected with in-situ measurements (Moldwin et al, 2000).…”
Section: Introductionmentioning
confidence: 68%
“…Similarly, small events are also detected with heliospheric imagers Sheeley and Rouillard, 2010) as well as in the corona, including eruptions from ephemeral regions and narrow CMEs Robbrecht, Berghmans, and Van der Linden, 2009;Schrijver, 2010), blowout Xray jets (Moore et al, 2010(Moore et al, , 2013, and streamer blobs (Wang, Zhang, and Shen, 2009;Sheeley et al, 2009). In parallel, much smaller FRs than typical MCs have been detected with in-situ measurements (Moldwin et al, 2000).…”
Section: Introductionmentioning
confidence: 68%
“…The convergent shape of each set of tracks is a characteristic of the corotating nature of the global structure (Rouillard et al, 2008); the tracks converge along a 'locus of enhanced visibility', indicated by green arrows (Sheeley and Rouillard, 2010). This locus marks the direction along the line-of-sight that is a tangent to the spiral formed by the series of emitted blobs, i.e.…”
Section: Methodology For Tracking Corotating Density Structuresmentioning
confidence: 99%
“…the CDS (see, e.g. Sheeley and Rouillard, 2010). To determine the time-dependent 3-D location of each CDS we select a single reference track in each pattern, corresponding to a single blob, and fit its trajectory by assuming that it moves radially outward at constant speed (the socalled 'fixed-phi' approximation).…”
Section: Methodology For Tracking Corotating Density Structuresmentioning
confidence: 99%
“…While they do not have the full PA coverage of SMEI, their location outside the Earth's magnetosphere removes noise sources that decreased the quality of SMEI images, such as energetic particle saturation from the cusp and South-Atlantic anomaly, glare from the moon, and the aurora. A number of large-scale solar wind transients have been tracked through the SECCHI field of view, including CMEs (e.g., Harrison et al, 2008;Davis et al, 2009;Möstl et al, 2010), corotating interaction regions (e.g., Sheeley Jr et al, 2008;Rouillard et al, 2008;Tappin and Howard, 2009), and solar wind "puffs" (e.g., Rouillard et al, 2010) and "blobs" (e.g., Sheeley Jr et al, 2009;Sheeley Jr and Rouillard, 2010).…”
Section: Heliospheric Imagersmentioning
confidence: 99%